Studies on the Physicochemical Properties of Ionic Liquids Based On 1-Octyl-3-methylimidazolium Amino Acids - Ben Ghanem, O. (American Chemical Society, 2015)
A series of new synthesized ionic liquids based on 1-octyl-3-methylimidazolium with glycinate, alaninate, serinate, prolinate, and asparaginate anions were prepared. Their thermophysical properties (density, viscosity, surface tension, and heat capacity) were measured at various temperatures and atmospheric pressures. Physicochemical properties such as thermal expansion coefficient values, molecular volume, standard molar entropy, and lattice energy standard were also determined using empirical methods. The effects of anions on the studied properties were further analyzed. Â© 2015 American Chemical Society.